Big data analytics and intelligence : a perspective for health care - Tanwar, Poonam; Jain, Vishal; Liu, Chuan-Ming; Goyal, Vishal (Emerald Publishing Limited, 2020)
Big Data Analytics and Intelligence is essential reading for researchers and experts working in the fields of health care, data science, analytics, the internet of things, and information retrieval.
Includes index.
Keywords: Big data.; Medical statistics.; Technology & Engineering -- General.; Data capture & analysis.; elektronické knihy; electronic books